2002
DOI: 10.1177/145749690209100405
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Sentinel Lymph Node Biopsy for Staging Anal Cancer

Abstract: Lymphoscintigraphy followed by dual-agent guided inguinal SLNB is technically feasible for staging patients with primary anal cancer. The detection of metastases in the removed sentinel lymph node(s) may alter the treatment and thus may improve the locoregional control and overall survival of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 11 publications
1
8
0
2
Order By: Relevance
“…ICG fluorescence imaging provided a detection rate of 83% which appears to be promising. The detection rate is comparable to those of other studies using the combined blue/radiocolloid method 5 but exceptional high rates of up to 100% have also been reported, 6 Clearly, a feasibility study involves a significant learning curve and other undetermined variables that can affect the results. Therefore, it is not worthwhile to compare these preliminary results with other more advanced diagnostic studies.…”
supporting
confidence: 71%
“…ICG fluorescence imaging provided a detection rate of 83% which appears to be promising. The detection rate is comparable to those of other studies using the combined blue/radiocolloid method 5 but exceptional high rates of up to 100% have also been reported, 6 Clearly, a feasibility study involves a significant learning curve and other undetermined variables that can affect the results. Therefore, it is not worthwhile to compare these preliminary results with other more advanced diagnostic studies.…”
supporting
confidence: 71%
“…As recently demonstrated by Mistrangelo and Morino [13], the method has been increasingly used to stage patients with anal cancer. After analyzing the results from the studies investigating SLN in that malignancy [8,[14][15][16][17][18][19][20], they recommend that SLN biopsy should be considered the procedure of choice for staging the inguinal basins in patients with anal cancer. In addition, they suggested that patients with negative SLN should be spared prophylactic inguinal radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We used a combined 99m Tc-labeled nanocolloid and Patent Blue technique to improve the yield of the SLNB technique with the lowest false negative rate 14,15. Currently, 8 studies with a total of 143 patients have been published that describe the feasibility of SLNB in patients with squamous carcinoma of the anal carcinoma 1623. These studies showed a high SLN detection rate of 96.5% (138 of 143).…”
Section: Discussionmentioning
confidence: 99%